Data Curation and Application of Statewide Data on Involuntary Assessment and Treatment in Behavioral Health - Christy, Annette; Ringhoff, Daniel; Rhode, Sara; Alitz, Paige (International Journal of Population Data Science, 2018)
Our university, based data center has curated statewide data on short-term, involuntary examinations for mental illness/co-occurring disorders for over two decades. We recently began receiving petitions and orders for longer-term civil commitment from Clerks of Court. We are currently developing a system to curate data on involuntary assessments/treatment for substance use disorders. The involuntary examination data have been used to produce 100+ ad hoc reports for a variety of stakeholders, a statutorily required annual report, as well as to inform the state legislature, advocates, agencies, and several statewide taskforces relating to criminal justice and mental health initiatives. Data from documents are currently received and entered in a) hard copy via the mail, b) securely scanned and transferred either via SFTP or with secure transfer to our University’s Box.com account, or c) direct provider entry into a secure web portal. Our University’s IT environment has evolved, with an escalation of organizational and policy changes related to the merging of two IT units. While this merging has led to innovation, it has also presented operational, organizational and logistical challenges. Discussed in this presentation will be a) these IT challenges, b) the pros and cons of form submission methods, c) how choice of submission method is informed by the capabilities of those submitting the documents in addition to, the resources and capabilities of our center within the context of current funding, as well as d) how this impacts choices made about data entry, data quality and use of the data for analyses.